Finlay Donovan is killing it - Cosimano, Elle (Cosimano, Elle. Finlay Donovan series, 2022)
Finlay Donovan is killing it... except, she's really not. She's a stressed-out single-mom of two and struggling novelist, Finlay's life is in chaos: the new book she promised her literary agent isn't written, her ex-husband fired the nanny without telling her, and this morning she had to send her four-year-old to school with hair duct-taped to her head after an incident with scissors. When Finlay is overheard discussing the plot of her new suspense novel with her agent over lunch, she's mistaken for a contract killer, and inadvertently accepts an offer to dispose of a problem husband in order to make ends meet... Soon, Finlay discovers that crime in real life is a lot more difficult than its fictional counterpart, as she becomes tangled in a real-life murder investigation